Perancangan Sistem HPWH (Heat Pump Water Heater) Pada Km. Meratus Karimata - Andriyan, Andriyan; Prayogi, Urip; Dwisetiono, Dwisetiono (Departemen Teknik Kelautan Universitas Hasanuddin, 2020)
The need for hot water on a ship is one of the facilities that must be obtained by the crew while carrying out their duties on the KM. Meratus Karimata is one of the ships that provide hot water as a facility for crew members. The heating system on this ship still uses the EHHW (Electric Heating Hot Water) heating system which will then be changed to the HPWH (Heat Pump Water Heater) system. This hot water need is based on the MLC (Marine Labor Convention) regarding the provision of recreational facilities on deck accommodation. The provision of hot water needs to be calculated and designed. The first thing to do is to calculate all distribution support components. Then the data for the needs of pumps with a power of 0.504 Kw, valves, shower taps, sink taps, pipe connections, and SCH 40 pipes with a diameter of Â¾